The efficacy of secukinumab with continued use in the treatment of psoriasis. (2nd January 2020) - Augustin, M.; Thaci, D.; Eyerich, K.; Pinter, A.; Radtke, M.; Lauffer, F.; Mrowietz, U.; Gerdes, S.; Pariser, D.; Lebwohl, M.; Sieder, C.; Melzer, N.; et al.
Summary: Affecting at least 100 million people worldwide, psoriasis is a disease causing red, scaly patches of skin that may cover a large area of the body and may also affect the nails, scalp, palms and soles. This can lead to a severe impairment in quality of life. For patients with moderate to severe disease, the use of drugs called biologic therapies can result in clear or almost clear skin. Since psoriasis is a long‐term condition, it is important for patients to experience long‐lasting effects from biologic therapies. However, some patients can eventually stop responding to biologic treatments, meaning the drugs no longer work. The extent to which patients stop responding, and rates of subsequent regain of response with continued treatment (meaning it starts working again), have not been studied at the level of individual patients. A study of a drug's continued ability to treat the disease (its efficacy) is known as a study of its stability. Secukinumab, a licensed biologic therapy for psoriasis, has shown long lasting efficacy and safety in large clinical trials. Treatment with secukinumab can achieve a 90% reduction of psoriasis within 16 weeks of treatment and long term efficacy has been demonstrated up to 5 years. In this study, investigators from Germany and the U.S.A. studied the stability of response to secukinumab in people who took part in two large clinical trials. They found that efficacy with secukinumab was stable over one year of treatment in most patients, and continued treatment with secukinumab resulted in a regain of efficacy after loss in some patients. Persistent loss of response was uncommon. Patient factors including body weight, previous biologic treatment failure and levels of the drug in the blood plasma could influence the stability of response. This summary relates to the study: Continued treatment with secukinumab is associated with high retention or regain of response Abstract : Linked Article: Augustin et al. Br J Dermatol 2020; 182 :67–75